2016
DOI: 10.1097/j.pain.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Ultramicronized palmitoylethanolamide in spinal cord injury neuropathic pain: a randomized, double-blind, placebo-controlled trial

Abstract: Neuropathic pain and spasticity after spinal cord injury (SCI) represent significant problems. Palmitoylethanolamide (PEA), a fatty acid amide that is produced in many cells in the body, is thought to potentiate the action of endocannabinoids and to reduce pain and inflammation. This randomized, double-blind, placebo-controlled, parallel multicenter study was performed to investigate the effect of ultramicronized PEA (PEA-um) as add-on therapy on neuropathic pain in individuals with SCI. A pain diary was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…In contrast, Andresen and colleagues report that a 12‐week treatment with PEA‐μm did not alleviate pain in patients with spinal cord injury‐induced neuropathic pain, compared to placebo‐treated patients (Andresen et al ., ). The authors however point out that the limited knowledge on PEA‐μm pharmacokinetics, including information on diffusion to the CSF, make it difficult to draw more specific conclusions.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 97%
“…In contrast, Andresen and colleagues report that a 12‐week treatment with PEA‐μm did not alleviate pain in patients with spinal cord injury‐induced neuropathic pain, compared to placebo‐treated patients (Andresen et al ., ). The authors however point out that the limited knowledge on PEA‐μm pharmacokinetics, including information on diffusion to the CSF, make it difficult to draw more specific conclusions.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 97%
“…Moreover, PEA administration lacked acute and chronic toxicity and was not associated with gastric mucosal lesions (Paladini et al, 2016). In contrast to these promising actions, a more recent report showed that um‐PEA as add‐on therapy was ineffective on neuropathic pain in individuals with SCI (Andresen et al, ). This negative outcome is not surprising considering that the study included patients (i) with different causes and severities of SCI and, more importantly, with an average time since injury of 10 years; (ii) receiving concomitant analgesic medication (dosing and length of treatment not specified); and (iii) with high pain scores at entrance (possibly indicating they were refractory to pain treatment) (Andresen et al, ).…”
Section: Pea and Pain Perceptionmentioning
confidence: 99%
“…32 A recent meta-analysis evaluating 12 clinical trials showed that PEA induces a time-dependent decrease of pain intensity not related to age or sex. 33 However, Andresen and co-workers, 34 evaluating the role of um-PEA as add-on therapy for neuropathic pain in 68 patients with neuropathic pain due to spinal cord injury, In all patients a significant decrease (P < .001) of values in both VAS and WOMAC scores was obtained after the first cycle (T1) of treatment (um-PEA 1200 mg/d) and was maintained up to the end of the study. T0 indicates admission; T1, 1 month after the beginning of the study; T3, 3 months after the beginning of the study, which represents the end of the study.…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta‐analysis evaluating 12 clinical trials showed that PEA induces a time‐dependent decrease of pain intensity not related to age or sex . However, Andresen and co‐workers, evaluating the role of um‐PEA as add‐on therapy for neuropathic pain in 68 patients with neuropathic pain due to spinal cord injury, failed to report any difference between um‐PEA and placebo treatment. In agreement with this article, in the present study we failed to demonstrate the effects of 2 months of treatment with um‐PEA on disability in patients with severe pain.…”
Section: Discussionmentioning
confidence: 99%